Kontrol Media Tiongkok di Era Xi Jinping sebagai Upaya Tiongkok menjadi Kekuatan Global - Esy Gracia (Jurnal Sentris, 2018)
In the era of globalization, media is omnipresent as well as gaining more influence and importance. With the rise of digital platform, the role of media as an information provider is enhanced and could prevail people’s political life. It is then clear that media is one of the pathways to become a Global Power due to its capability to direct public opinion. China in Xi Jinping’s era, fully recognizing the media’s potential, is continuing its effort on maintaining control over the media to be able to secure its prominence and level up its position in the international system. Using the concept of agenda setting and Uighurbiz website case as the example, this paper seeks to understand China’s control over its media in order to ease their way to becoming a global power.